Antioxidant activity, total phenolic content and biotransformation of isoflavones during soy lactic‐fermentations. Issue 6 (17th May 2021) - Lodha, Dikshita; Das, Sujit; Hati, Subrota
Abstract: The present study aimed to enhance the antioxidant activity of soymilk with biotransformation of soy bio components like daidzin and genistin while lowering the total phenolic content. Ten lactobacilli cultures were used to produce the β‐glucosidase in a soymilk medium, and the biofunctional properties of soymilk were also investigated. Four out of 10 lactobacilli cultures were selected based on their ability to produce the most β‐glucosidase in soymilk medium. Selected lactobacilli cultures were further used for the evaluation of antioxidant activity, total phenolic content, and biotransformation of isoflavones during soy lactic fermentation. In this study, M4 ( Lactobacillus fermentum ), KGL3A ( Lactobacillus plantarum ), M16 ( Lactobacillus fermentum ), and M9 ( Lactobacillus rhamnosus ) strains were found to produce the highest β‐glucosidase compared to other strains. We have investigated the antioxidative activity of soymilk fermented with M9 and KGL3A, and it was found to be significantly higher ( p < .05) as compared to unfermented soymilk, also M4 and M9 strains have the ability to drastically reduce the total phenolic contents in both soymilks during fermentation. Furthermore, the biotransformation of glucoside‐conjugated isoflavones to its corresponding aglycones by KGL3A strain was significantly ( p < .05) higher at 24 hr of fermentation. Therefore, these selected strains could be recommended for the development of aglycone‐rich soy fermented foods having a high level of antioxidant activity. Novelty impact statement: The demand for non‐dairy products worldwide, especially fermented milk from plant sources, has resulted in a growing number of vegan consumers who are opting for plant‐based milk substitutes for their diet, nutrition, and prevention against several chronic diseases. In this study, four Lactobacillus cultures, KGL3A ( L . plantarum ), M4 ( L . fermentum ), M16 ( L . fermentum ), and M9 ( L . rhamnosus ) strains have shown promising results during fermentation of soymilk, which was prepared from soybeans (AAU, NRC 37) and commercially available soymilk (Sofit). Therefore, these potent Lactobacillus strains could be used for the production of fermented soymilk foods having higher antioxidative activity and soy aglycones.